Contextual determinates of under-five malnutrition in mining communities: a critical review of nutrition interventions for optimal impact - Herbert Tato Nyirenda; David Mulenga; Hilda Nyambe-Silavwe (Frontiers in Public Health)
PurposeMalnutrition continues to be a widespread and critical public health issue, yet there is a lack of comprehensive evidence synthesizing empirical findings and assessing the practicality of nutrition interventions in diverse contexts. This paper analyzes contextual data to establish a benchmark for selecting effective nutrition strategies, thereby maximizing their impact and ensuring targeted, sustainable outcomes.MethodsThis study employed a cross-sectional design to examine the key drivers of nutrition in mining communities, focusing on children under five and their caregivers. A sample of 711 participants was selected using a systematic random sampling technique. Data collection involved structured questionnaires, direct measurements of children, and interviews with caregivers. Anthropometric measurements were conducted according to WHO standards to assess underweight status. Statistical analysis included descriptive statistics and chi-square tests to evaluate the effectiveness and feasibility of context-specific nutrition interventions.ResultsChi-square analysis highlights a complex interplay of factors influencing underweight in children under 5 years of age, including expenditure priorities (p = 0.002), access to resources such as primary grocery stores (p = 0.001) and farmers’ markets (p < 0.001), food preparation practices (p = 0.006), agricultural empowerment (p < 0.001), and feeding styles/strategies (p = 0.004). Multivariate logistic regression further reveals that key determinants of child underweight include age (aOR = 15.24, p < 0.001), caregiver disability or chronic illness status (aOR = 0.14, p < 0.001), inadequate food production (aOR = 1.94, p = 0.009), and expenditure priorities (aOR = 2.46, p = 0.007). These factors collectively highlight the multifaceted nature of child undernutrition.ConclusionThe findings highlight the critical importance of considering contextual factors when developing nutrition interventions. Key elements such as expenditure priorities, access to food resources, food preparation practices, agricultural empowerment, and feeding strategies play a significant role in shaping child nutrition outcomes. Understanding these factors is essential for designing interventions that are not only effective but also sustainable and culturally appropriate.